Bandwidth enhancement of a narrowband rectangular microstrip antenna on a spiral fan-shape Electromagnetic Band-Gap (EBG) patch structure - Masri, Thelaha; Rahim, Mohamad Kamal A.; Jamaluddin, Mohd Haizal; Asrokin, A. (2006)
An innovative and novel technique has been explored in enhancing the bandwidth of a rectangular patch antenna by introducing a spiral fan-shape electromagnetic band gap (EBG) structure between a narrowband patch antenna and its ground plane. Measured result shows an excellent return loss and good impedance matching which resulted in an increment of the bandwidth from about 4 % for a single layered narrow band rectangular microstrip patch, to more than 17 % after the EBG structure was introduced. This paper present the methodology, simulations and experimental works carried out in accomplishing the objective above. Microwave Office 2006 software has been used to initially simulate and find the optimum design and results.